Model Kebijakan Pemerintah dalam Pengaturan Pemanfaatan Sumber Daya Hayati oleh Negara Asing di Wilayah Pengelolaan Perikanan Indonesia - Author: Irawati (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research discusses: First, the practices of states in marine natural resources utilization by foreign countries. Second, regulation model of marine natural resources utilization by foreign countries to be able to give contribution for fishery industry in Indonesia. The method used in this research was normative juridical, The conclusions are first¸ the practices of coastal states in marine natural resources utilization by foreign countries have complied with the international sea law provisions considering some aspects, namely conservation, economic, and culture. Second, regulation and implementation models of natural resources implementation in Indonesia fishing area that can develop fishery industry in Indonesia are through an integrated fishing company by the establishment of a joint-venture company. This research discusses: First, the practices of states in marine natural resources utilization by foreign countries. Second, regulation model of marine natural resources utilization by foreign countries to be able to give contribution for fishery industry in Indonesia. The method used in this research was normative juridical, The conclusions are first¸ the practices of coastal states in marine natural resources utilization by foreign countries have complied with the international sea law provisions considering some aspects, namely conservation, economic, and culture. Second, regulation and implementation models of natural resources implementation in Indonesia fishing area that can develop fishery industry in Indonesia are through an integrated fishing company by the establishment of a joint-venture company.